1978
DOI: 10.1149/1.2131359
|View full text |Cite
|
Sign up to set email alerts
|

On the Diffusion of Excess Vacancies to Free Surfaces and Voids in Thin Films

Abstract: Recent investigations have,shown that resistivity decay in evaporated gold films originates, in part, from the annihilation of excess vacancies, trapped during film condensation, at a high density (1015-1{~17/cm 8) of small (~50A) voids present within the film. This paper presents a theoretical treatment of vacancy diffusion to free surfaces and to voids. The treatment predicts both the observed void growth and resistivity decay in thin films.It is well known that the resistivity of freshly deposited thin film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1979
1979
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…After the cessation of film deposition a further decrease in resistance is observed as vacancies diffuse from the bulk to the surface, improving film continuity. Similar effects in gold were observed by others (9). It should be noted that no such effect was observed after deposition of nickel films; i.e., once deposited their resistance remained constant.…”
Section: Apparatus and Experimental Proceduressupporting
confidence: 87%
“…After the cessation of film deposition a further decrease in resistance is observed as vacancies diffuse from the bulk to the surface, improving film continuity. Similar effects in gold were observed by others (9). It should be noted that no such effect was observed after deposition of nickel films; i.e., once deposited their resistance remained constant.…”
Section: Apparatus and Experimental Proceduressupporting
confidence: 87%
“…Although presently available analytical instruments cannot image individual vacancies, a transmission electron microscope ͑TEM͒ can detect aggregates of vacancies, i.e., voids. In fact, the existence of excess vacancies in vapor-deposited gold films was first demonstrated 11 using TEM, which revealed void growth that occurred at the expense of excess vacancies. The concentration of excess vacancies in thin films has been reported to reach well beyond their equilibrium value, often as high as a few atomic percent ͑atom %͒.…”
Section: Introductionmentioning
confidence: 99%
“…We investigated why such a sudden morphology change occurs within a short period of time after the deposition and concluded that this particular film behavior appears to be stress-related. Consideration of the intrinsic properties of thin-film microstructures in the literature [10][11][12][13][14] suggests that as-deposited copper contains a high concentration of excess vacancies, which promote the development of a tensile stress during their annihilation processes. 9 Such deposits are initially in an expanded state due to volume occupied by excess vacancies but begin to shrink during room-temperature aging as the vacancies are annihilated at the surface and grain boundaries.…”
mentioning
confidence: 99%
“…The stress level may be affected considerably by the flow of vacancies to the film surface and by structural defects. 8 It has also been suggested that, during thin film grain growth, the removal of grain boundaries-and hence the reduction of excess volume in the grain boundaries-will induce stress in the film when it is constrained by the substrate. 8 Little work has been done, to the best of our knowledge, on the stress relaxation of multicomponent oxide thin films.…”
Section: Introductionmentioning
confidence: 99%
“…8 It has also been suggested that, during thin film grain growth, the removal of grain boundaries-and hence the reduction of excess volume in the grain boundaries-will induce stress in the film when it is constrained by the substrate. 8 Little work has been done, to the best of our knowledge, on the stress relaxation of multicomponent oxide thin films. 9 In this work, an in situ stress measurement technique was employed to investigate the kinetics and mechanisms of stress relaxation in PbTiO 3 thin films.…”
Section: Introductionmentioning
confidence: 99%